(untitled) (Contemporary Journal of Social Science Review, 2025)
Dialogues are the sources of communication between people. Dialogues are always used to show any particular relation with objects. Objects can be physical things, concepts, and ideas. The words in dialogues remain same for different ages, but their usage and meaning vary from person to person due to variant socio-historical backgrounds. Dialogues used in literary texts also associate the author and readers with each other (Bakhtin, 1984). keeping in view this concept, this study applies Mikail Bakhtin’s concept of Dialogism (1984) on Sur Sussai” from “Shah Jo Risalo (1992). The findings of the study show that the main character, Sussai, narrates her life struggle in dialogic form. She reveals her sincere, faithful, and true love for her lover, Punhu. In dialogic form, she expresses her love for Punhu and reveals that deep love for her lover is not letting her to sit in one place and wait for him, but it is creating more pain and sorrows within. Therefore, she leaves her home and starts a journey in search of Punhu. Moreover, the dialogues in story of Sussai enable readers to associate it with social life and uncover many hidden realities of life. At the social level, the story shows that in Sindh`s past history, women have remained strong and bold in terms of their love, affection, and intimacy. Sussai passed through many disasters and faced hurdles in the search for Punhu, but never lets her intentions fade. She stands firm like a rock and continues her struggle to find the love. Hence, the study emphasizes that Sussai’s untiring struggle sets the background that the aim of life is not achieved just by sitting in one place, but one needs to come out of the comfort zone, continue life struggle and move forward with a meaningful purpose. Moreover, this Sur and it’s dialogic conversation is also full of spiritual concepts as well. It stresses that one does not need to search God from the external sources; God lives within. There is just a need to know thyself.